(untitled) (Journal of Social Sciences Review, 2023)
The River Swat is one of Pakistan’s interior rivers, lying in the Khyber Pakhtunkhwa province. Despite being semi-dry, the area is a significant grain and fruit-producing area. However, persistent drought in recent years, along with excessive water extraction, has resulted in a constant decline of water pouring into the Swat River’s mainstream, resulting in serious deterioration of ecosystems along the river’s lower reaches. Water pricing is the best tool to control the misuse of water resources and will lead to the optimum use of this very precious resource. 300 farmers were chosen randomly and a preliminary test of the quantitative questionnaire was conducted before data collection to ensure clarity. To analyze the quantitative dataset Multinomial Logistic Regression, a version of ordinary regression was used. Farmers in the study area who face a 100% rise in water prices were polled to gauge their reactions. The results reveal that factors that are "total land area", "age", "total farm income", "slight water shortage", & "presence of fruit plants" are statistically significant. According to the finding, many farmers reacted to the rise in irrigation water prices and they were ready to use irrigation water more efficiently. This study also observed and concluded that just raising the irrigation water price is not a realistic and permanent solution.